Distal Clavicular Osteochondral Autograft Augmentation for Glenoid Bone Loss: A Comparison of Radius of Restoration Versus Latarjet Graft. Issue 5 (April 2018) - Kwapisz, Adam; Fitzpatrick, Kelly; Cook, Jay B.; Athwal, George S.; Tokish, John M.
Background: Bone loss in shoulder instability is a well-recognized cause of failure after stabilization surgery. Many approaches have been described to address glenoid bone loss, including coracoid transfer. This transfer can be technically difficult and has been associated with high complication rates. An ideal alternative to coracoid transfer would be an autologous source of fresh osteochondral graft with enough surface area to replace significant glenoid bone loss. The distal clavicle potentially provides such a graft source that is readily available and low-cost. Purpose: To evaluate distal clavicular autograft reconstruction for instability-related glenoid bone loss, specifically comparing the width of the clavicular autograft with the width of an ipsilateral coracoid graft as prepared for a Latarjet procedure. Further, we sought to compare the articular cartilage thickness of the distal clavicle graft with that of the native glenoid. Study Design: Controlled laboratory study. Methods: Twenty-seven fresh-frozen cadaver specimens were dissected, and an open distal clavicle excision was performed. The coracoid process in each specimen was prepared as has been described for a classic Latarjet coracoid transfer. In each specimen, the distal clavicle graft was compared with the coracoid graft for size and potential of glenoid articular radius of restoration. The distal clavicle graft was also compared with the native glenoid for cartilage thickness. Results: In all specimens, the distal clavicle grafts provided a greater radius of glenoid restoration than the coracoid grafts ( P < .0001). On average, the clavicular graft was able to reconstruct 44% of the glenoid diameter, compared with 33% for the coracoid graft ( P < .0001). The articular cartilage of the glenoid was significantly thicker (1.4 mm thicker, P < .0001) than that of the distal clavicular autograft (average ± SD, 3.5 ± 0.6 mm vs 2.1 ± 0.8 mm, respectively). When specimens with osteoarthritis were excluded, this difference decreased to 0.97 mm when compared with the clavicular cartilage ( P = .0026). Conclusion: The distal clavicle autograft can restore a significantly greater glenoid bone deficit than the Latarjet procedure and has the additional benefit of restoring articular cartilage to the glenoid. The articular cartilage thickness of the distal clavicle is within 1.4 mm of that of the native glenoid. Clinical Relevance: The distal clavicular autograft may be a suitable option for reconstruction of instability-related glenoid bone loss. This graft provides a structural osteochondral autograft with a broader radius of reconstruction than that of a coracoid graft, is locally available, has minimal donor site morbidity, is anatomic, and provides articular cartilage.